Pembuatan Orange Marmalade Di Pulau Belimbing 1 Desa Kuok Kecamatan Kuok Kabupaten Kampar Sebagai Produk Khas Oleh – Oleh Desa Kuok - Angga Pramana; Farida Hamzah; Priscila Gultom; Okri Reval; Suci Rahmayani; Syawatul Mutiara (Journal of Community Engagement Research for Sustainability, 2021)
Kuok is a sub-district in Kampar Regency, Riau, Indonesia which has an area of 6,000 ha. The majority of the population in Kuok village is broken-eyed as farmers, where the most cultivated agricultural community is citrus plants. Citrus agricultural products are still managed in the form of fresh because it is carried out diversification of citrus derivative products in the form of the manufacture of orange marmalade products by the UNRI community service team. The purpose of this community service is to make a product of diversification of derivatives in citrus fruits namely orange marmalade so that oranges are not only consumed in fresh form and increase people's income. The methods used are surveying, socialization and training. The result is orange marmalade has a sweet taste and is a little bitter because of the influence of additions to the skin, the texture is thick and the color is greenish-yellow. Orange marmalade is generally almost the same as jam only the difference is the addition of orange peel.